Pendukung Waktu Kunjungan Dini Wanita Pekerja Seks ke Klinik Infeksi Menular Seksual di Denpasar - Putu Cintya Denny Yuliyatni; Komang Ayu Kartika Sari (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Female sex workers (FSW) are recommended routine to do a screening of Sexually Transmitted Infection (STI) clinics because they are the risk group. The Integrated Biological and Behavioral Survey of Indonesia showed a low number of FSW return visits to STI services in the last 3 months. The study aimed to determine the factors of the early visits of FSW to the STI clinic. This research was a cross-sectional of 102 FSW samples taken consecutively. Data analysis using the chi-square test and multiple logistic regression. The results were obtained that: of the total sample, the majority (69.6%) were direct FSW, secondary education (56.9%), and had no health insurance (72.5%). Only 23.5% of FSWs returned screening in 3 months. Multivariate analysis results showed direct FSW (aOR=9.11;CI95%=1,835-45,283), who rarely/never use condoms with customers (aOR=4.69;CI95%=1,631-13,535) and who had no insurance (aOR=3.18;CI95%=1,017-9,940) returned to STI clinic more earlier (≤3 months) than other groups. The low return of FSW and its determinants need attention. Outreach strategies by field staff based on the type of FSW and the adjusted outreach materials are needed to increase the return of FSW to STI services.